Non-additive mixture effects of benzo[a]pyrene and pesticides in vitro and in vivo: Role of AhR signaling. (1st January 2023) - Ünlü Endirlik, Burcu; Wincent, Emma; Dreij, Kristian
Abstract: Polycyclic aromatic hydrocarbons (PAHs) and pesticides are two major groups of environmental contaminants which humans are simultaneously exposed to. However, potential mixture interactions of these groups of chemicals are not well-studied. In this study, the effects of binary mixtures of the PAH benzo[ a ]pyrene (B[ a ]P) and the commonly used pesticides chlorpyrifos, paraquat and tebuconazole on human liver HepG2 cells were investigated. The results showed that binary mixtures of B[ a ]P and paraquat or tebuconazole mainly caused additive effects on cell viability and cytochrome P4501a1 ( CYP1A1) expression compared to single compound exposures. In contrast, the binary mixture with chlorpyrifos interacted antagonistically on cell viability and ROS production, whereas synergistic effects were observed for induction of CYP1A1 expression. B[ a ]P and chlorpyrifos also inhibited the activity of recombinant human CYP1A1 enzyme. To verify the synergistic in vitro results, zebrafish ( Danio rerio ) embryos were exposed to binary mixtures of B[ a ]P and chlorpyrifos. The mixtures caused synergistic induction of CYP1A expression, as well as synergistic developmental toxicity on multiple endpoints including non-inflated swim bladder, yolk-sac and pericardial edema, and spinal deformation. The effects were reduced upon morpholino-mediated knockdown of the aryl hydrocarbon receptor (AhR), indicating an AhR-dependence of the synergistic toxicity. Altogether, these data suggest that the combination of AhR activation and CYP1A1 inhibition is responsible for the underlying non-additive interaction between B[ a ]P and chlorpyrifos in vitro and in vivo . Graphical abstract: Image 1 Highlights: B[ a ]P with tebuconazole or paraquat caused additive effects in vitro . B[ a ]P with chlorpyrifos induced synergistic CYP1A1 expression in vitro . B[ a ]P with chlorpyrifos induced synergistic toxicities in developing zebrafish. Synergism likely caused by chlorpyrifos CYP1A inhibition and sustained B[ a ]P levels. Functional knockdown of AhR significantly reduced the mixture effects in vivo .